An analysis of shari’ah audit practices in Islamic banks in Malaysia - Nur Laili Ab Ghani; Abdul Rahim Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2015)
According to the Shari’ah Governance Framework (Bank Negara Malaysia 2011), each Islamic bank and Islamic fi nancial institution in Malaysia is required to establish the Shari’ah audit function. The Shari’ah audit function, according to the Framework, is instituted in order to provide reasonable assurance and to ensure an effective internal control system for Shari’ah compliance. A review of the literature on this topic shows a lack of empirical studies that explain the Shari’ah audit practices in Islamic banks. This study examines the extent of Shari’ah audit practices in Islamic banks in Malaysia. The study employs survey questionnaires which were distributed to the Heads of Shari’ah audit, internal Shari’ah auditors, Shari’ah executives and members of the Shari’ah Committee of 16 Islamic banks in Malaysia. The study used the Exposure Draft of Internal Shari’ah Audit Framework (ISAF) issued by the International Shari’ah Research Academy (ISRA) as a benchmark to measure the extent of Shari’ah audit practices. The results of the study indicate that the majority of the Islamic banks have properly established the audit objectives, the governance structure, the competency requirements, the audit process, and the reporting requirements as part of their Shari’ah audit practices. However, some Islamic banks have not clearly spelled out the audit scope and the audit charter. The study also found that internal auditors, Shari’ah executives and members of the Shari’ah Committee mostly agreed on the importance of developing a proper structure for the Shari’ah audit function. In conclusion, the reasonably good Shari’ah audit practices present in Islamic banks are commendable and indicate a positive development in enhancing the integrity and the accountability of Islamic banks, especially in Malaysia.